Health News and Media Manipulation: An Examination of Health Reporting, and What This Means for Journalism Today - Kibby, Joanna Yevily (Auckland University of Technology, 2002)
This thesis will investigate, firstly, the presentation and handling of health news and ‘miracle cures’ by the media today and, secondly, what this in turn means for journalism, particularly New Zealand journalism. The series of stories written and produced about Lyprinol, a mussel extract reported by the New Zealand media to be a miracle cancer cure, will be used to help illustrate some of the points raised about the media’s coverage of health and related issues. I employed the Political Economy context throughout this thesis, looking in particular at how news organisations are constrained and shaped by the political and economic environment in which they operate, and how this in turn shapes the news that they produce. I looked specifically at the increasingly intimate relationships between the media and health organisations and drug companies, the commercialisation and subsequent sensationalism of the news, the traditional and ideal roles that the media should play in modern society, and finally, what can or should be done, if anything, in order to make the media more accountable and responsible for their actions. This thesis will show that commercialisation is a determining factor and, subsequently, sensation is a pervasive feature, of much of what the media produces about health and related issues. This thesis will also contend that the media’s presentation of health and ‘miracle cures’ is both harmful and misleading – enough to justify introducing new or more effective ways of making the media more responsible and accountable to the public, whom it is undoubtedly their duty to serve.
Keywords: Journalism; Medical